Examining the Technological, Pedagogical and Content Knowledge of Nepalese Teacher Educators - Laudari, Suman; Prior, Julia (Journal of NELTA, 2020)
Teacher-educators’ TPACK profile suggests whether and/or to what extent they can help future teachers to develop competencies required to teach with technology. However, teachers-educators’ digital competencies are not well understood because of the limited number of research studies. This study contributes to the existing body of knowledge by providing insights into the Nepali teacher-educators’ competencies in the use of educational technology. The study collected data from 153 teacher educators from 63 teacher education campuses in Nepal using a TPACK questionnaire combined with an ICT confidence survey. The findings reveal that teacher educators were more confident about their pedagogical knowledge (PK) and content knowledge (CK) than their technological knowledge (TK) and technological, pedagogical and content knowledge (TPACK). The findings suggest that the teacher educators lacked competencies to teach and to demonstrate technology integration in educational practice. The implication of this finding is that pre-service teachers will miss the opportunity to gain the skills and knowledge required to use technology in their future practice.